Indonesian EFL Students’ Voices on Utilizing Grammarly Application to Facilitate Writing Skill in Recount Text - Siti Mariam; Catur Kepirianto; Mualimin; Reza Kafipour (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2024)
In order to help EFL students grasp the simple past tense in writing skills for recount texts, this study intends to provide students perspectives on using the Grammarly application as an online grammar checker. The qualitative approach was used together with a narrative inquiry research design. In depth interviews employed a method of data collection. The research participants were two female English Education Department students and a male student of English Department at two different universities in Central Java, Indonesia, in the academic year 2022-2023. The study's findings indicate that every participant thought using the Grammarly application to write recount texts helped them learn how to use the simple past tense. It boosts students in composing recount text, because the function as automated writing evaluation feedback. It means that Grammarly application can minimize writing anxiety, even if they encounter certain challenges when utilizing the application.